Multilocus identification and pathogenetic characterization of Colletotrichum endophyte and pathogen species isolated from cocoa leaves and pods (Theobroma cacao) in Ecuador - Espinoza-Lozano, Fernando (2025)
Cacao cultivation is one of the main agricultural products of Ecuador, known internationally for its quality and aroma. However, it is affected by fungal diseases including Moniliophthora roreri, Moniliophthora perniciosa, Phytophthora spp., and Colletotrichum spp. The genus Colletotrichum spp. is known for its characteristics that complicate traditional taxonomic identification. In cacao cultivation, it is one of the most frequently found species as an endophyte of leaves and fruits, yet it is also reported to cause the disease known as anthracnose on leaves and fruits. The objective of this work was to identify at the species level 16 Colletotrichum isolates, 13 from healthy leaf endophytes and 3 from pods with symptoms, through multilocus analysis of the ITS1, 5.8S, and ITS2 region, and partial sequences of the TUB2 and GAPDH genes. Subsequently, their pathogenicity was evaluated by inoculating healthy cacao pods and measuring the damage caused. The 16 isolates were identified as follows: from the gloeosporioides complex, C. siamense 6, C. chrysophilum 6, C. theobromicola 2 and from the boninense complex, C. karstii 2. The most frequently found species were those that caused symptoms, especially C. siamense, to which the strains were isolated from symptomatic pods belonged. This work provides relevant and accurate information about the diversity of Colletotrichum species that colonize cocoa plantations and identifies which species might cause the disease known as anthracnose. Additionally, it allows for a more precise diagnosis and consequently better treatment.